Herpes Simplex Encephalitis: Successful Treatment with Acyclovir - Heidari, Aliehsan; Kalantar, Enayatollah; Dehghan, Mohammad Hosein; Fallah, Parviz (Archives of Advances in Biosciences, 2019)
Introduction: One of the most common causes of encephalitis is due to viral infections, such as herpes simplex. Traditionally, brain biopsy was required for the diagnosis of HSV encephalitis; however, here CSF PCR detection for herpes simplex encephalitis is reported which was successfully treated with Acyclovir.Case presentation:A 52 year old female patient was brought to emergency department with fever (400C), constipation, abdominal pain, fatigue, disorientation and agitation for the last two days. DNA extraction and Real Time PCR was performed on CSF sample for HSV-1/2 and HSV-1 was positive. Moreover, the brain MRI report showed left and basal temporal oppression, together with left and basal frontal pus. The patient was discharged after 20 days of hospitalization and treatment with acyclovir and normal physiological indexes and had a good clinical and neurologic outcome with resolution of all the symptoms.Conclusion:It is worthy to emphasize that despite the normal biochemical CSF, imaging results and PCR are proved evidence of HSV encephalitis.